A randomized placebo controlled trial of Mitomycin - C in surgical outcome of primary endoscopic dacryocystorhinostomy - A.S. Harugop; B.K. Rekha; R.S. Mudhol; N.D. Zingade; S.M. Hugar; A.T. Das; M. Maheswaran (Al Ameen Medical College, 2013)
Objective: To compare the patency of the stoma and relief of epiphora after endoscopic dacrocystorjinostomy (EnDCR) surgery with Mitomycin C and Placebo in cases of chronic dacrocystitis secondary to primary post saccal stenosis. Design: Randomised placebo controlled trial. Materials & Methods: 40 patients (20 cases with Mitomycin - C and 20 cases of Placebo) diagnosed to have chronic dacrocystitis underwent EnDCR. Using single randomised trial, the rhinostomy site was applied with Mitomycin - C 0.2 mg/ml or placebo for 3 minutes by means of a gelfoam and was washed with 10 ml normal saline. Average time taken for the procedure was 40 minutes. Local massage, serial sac syringing was done on the 3rd, 7th & 14th post - operative day and nasal douching were performed during the follow - up period. Endoscopic suction clearance was done weekly for 1 month, then monthly for 6 months to prevent crusting and adhesions. Follow - up examination was done with an endoscope by the same surgeon at the end of 1 week, 1 month and then monthly ranging from 3 months to 18 months. The surgical outcome was evaluated both subjectively and objectively. Results: The overall success rate by subjective assessment at the end of 6th month was 95% in Mitomycin C group compared to 80% in the placebo group. But there was no statistical difference between the surgical outcomes on the basis of subjective evaluation (p= 1). Objective endoscopic assessment revealed that the rhinostomy stoma was visible in 16 (80%) patients with Mitomycin C compared to 14 (70%) patients with placebo, but there was no statistical difference between the 2 groups (p = 0.4053). Failure was observed at the end of 6th month in 1 case (5%) with Mitomycin C compared to 2 cases (10%) in the placebo group. Conclusion: EnDCR along with Mitomycin C application helps in preventing the closure of rhinostomy stoma and is preferred treatment of choice in case of chronic dacrocystitis with higher safety, success rate and minimal post - operative complications.